El método lúdico para el desarrollo del lenguaje oral de los niños de 4 a 5 años, en la Escuela de Educación Básica Dr. José́ Mariano Borja, parroquia Cajabamba, cantón Colta provincia de Chimborazo, período octubtre 2020 – marzo 2021 - Guailla Pilco, María Tomasa (2021)
This study aims to understand the importance of using of the ludic method to develop oral language in children from 4 to 5 years old attending Mariano Borja Elementary School. The main goal of this study was to develop oral language through the application of the ludic method in children aged 4-5 years attending José Mariano Borja Elementary School. The methodology used to achieve the research goal was fieldwork and bibliographic. A total of thirty-three children at their initial level participated in this study. The results obtained allowed to establish that the ludic method is important for the development of oral language as well as the use of resources that agree with this method. The results suggest that using these elements increased children’s oral production. In addition, a pictographic story was used. This study used observation as a method to collect data. Observations were recorded in an observation protocol. Observations evidenced that the level of development of oral language using the ludic methodology reaches 75%. The main conclusion was that the level of oral development of the children was evaluated through ludic activities that were recorded in an observation record, where it was evidenced that 56% of the children performed the activity but did not retain the information. Consequently, children have not managed to develop oral language.